Analysis Delay Budget Absorption the Work Unit of KPPN Singaraja - Ni Putu Dina Hani Saputri; I M A Putrayasa; I Nyoman Sugiarta (Journal of Applied Sciences in Accounting, Finance, and Tax, 2021)
At the end of 2019, precisely in December, a new Covid-19 virus outbreak was discovered in Wuhan, China. The emergence of this virus was first detected in Indonesia in March 2020. Since this virus first appeared in Indonesia, the government immediately issued a new policy, namely refocusing and reallocating the APBN expenditure budget, as well as accelerating the procurement of goods/services for health facilities, such as drug procurement. - Medicines and medical devices. As a result of this refocusing and reallocation of the APBN budget, the absorption of the expenditure budget has accumulated at the end of the year. This accumulation of budget absorption tends to be low at the beginning of the year and soaring high at the end of the year. The purpose of this study is to determine the factors that cause the accumulation of budget absorption due to Covid-19. This type of research is descriptive qualitative with transcendental phenomenology. The data analysis technique used is Miles & Huberman. The data in this study were obtained through literature study, document analysis, observation, and interviews. The results of this study indicate that changes in the budget, human resources, and procurement of goods/services cause the accumulation of budget absorption.